ANALISIS CERITA RAKYAT “SASAKALA DESA KALAPA GENEP” MENGGUNAKAN ASPEK SINTAKSIS, SEMANTIK, DAN PRAGMATIK - Anas, Ridwan (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. This research is deeply based on the oral narrative "Sasakala Kalapa Village Genep" with a major focus on syntaxical, semantic, and pragmatic aspects. The background of the research was triggered by the researcher's curiosity and curiosity to continue the previous research, emphasizing the three aspects in the context of the oral story. Qualitative descriptive methods are chosen to accurate research results. The aim of the research is to describe the natural data of the story as clearly as possible and to link it to the context of its existence in the society of its owners. The object of study is folk stories, including the origin of place names and events, which develop through tradition and oral transmission. Though the truth is questioned as it has evolved for a long time, the story is regarded as a legacy of ancestors that evolved downwardly through the way of speech. The study procedure involves analysis of text structure (syntax), semantic aspects (character, consolidation, and setting), as well as pragmatic aspects. (konteks narasi, proses penciptaan, pewarisan, dan fungsi). Results and discussion: The study makes a significant contribution to understanding the sustainability of traditional oral storytelling, by highlighting findings in syntax, semantic, and pragmatic aspects. It enriches our view of the role of people's stories in preserving local identity and wisdom, providing indepth insight into the cultural heritage that is inseparable from the life of the village of Kalapa Genep.